Aboriginal customary law : a source of common law title to land - Secher, Ulla (Oxford : Hart Publishing, 2014)
Described as'ground-breaking' in Kent McNeil's Foreword, this book develops an alternative approach to conventional Aboriginal title doctrine. It explains that Aboriginal customary law can be a source of common law title to land in former British colonies, whether they were acquired by settlement or by conquest or cession from.
Part I: Australian Land Law and the Meaning of Radical Title Pre-Mabo -- Chapter One: The Origin and Application of the Doctrine of Absolute Crown Ownership in Australia: The Common Law 1788-1992 -- Chapter Two: The Meaning of Radical Title Pre-Mabo--Part II: The Doctrine of Tenure and the Juridical Consequences of the Colonial Law Classification of an'Inhabited' Colony as'Settled' Re-examined Post-Mabo -- Chapter Three: The Doctrine of Tenure and the Common Law Consequences of the Classification of an'Inhabited' Colony as'Settled' Post-Mabo: Emergence of the Doctrine of Tenure ad Veritatem and the Doctrine of Continuity Pro-Tempore -- Part III: The Meaning of Radical Title in Post-Mabo Australian Jurisprudence -- Chapter Four: Radical Title and Unalienated Land Post-Mabo -- Chapter Five: Radical Title: Lessons from the Sea -- Part IV: The Practical Implications of the Crown's Radical Title -- Chapter Six: Crown Acquisition of a Plenary Title: The Common Law Record Requirement and Statutory Regimes Regulating the Alienation of Land -- Chapter Seven: The Doctrine of Common Law Aboriginal Customary Title in Australia and Implications for South Africa -- Chapter Eight: Canada: Application and Implications of the Doctrine of Common Law Aboriginal Customary Title -- Conclusions.
Includes bibliographical references and index.
Keywords: Land tenure -- Law and legislation -- Australia; Aboriginal Australians -- Legal status, laws, etc; Customary law -- Australia